ЕКОЛОГІЧНА МОДЕРНІЗАЦІЯ ЕКОНОМІКИ ЯК НЕОБХІДНА УМОВА СТАЛОГО РОЗВИТКУ СУСПІЛЬСТВА (ІННОВАЦІЙНА ЕКОНОМІКА, 2020)
Печенюк А.В., Печенюк А.П. ЕКОЛОГІЧНА МОДЕРНІЗАЦІЯ ЕКОНОМІКИ ЯК НЕОБХІДНА УМОВА СТАЛОГО РОЗВИТКУ СУСПІЛЬСТВАМета. Дослідження передумов екологізації виробництва в Україні та обґрунтування механізму реалізації ефективної екологічної модернізації виробництва.Методика дослідження. Теоретичною та методологічною базою дослідження стали фундаментальні положення сучасної економічної науки та результати досліджень вчених у сфері екологізації виробництва. При цьому використано низку загальнонаукових методів: теоретичного узагальнення – для дослідження історичних аспектів становлення та розвитку екологічної модернізації виробництва; аналізу та синтезу – при визначенні факторів, які стримують темпи впровадження новітніх екологобезпечних технологій в Україні; управлінського моделювання – для розробки комплексу заходів з активізації екологічної модернізації виробництва; логічний – для обґрунтування переваг, які отримує підприємство, інвестуючи ресурси у високотехнологічні екологобезпечні технології.Результати дослідження. Досліджено негативні наслідки антропогенного впливу на довкілля, розкрито передумови природоохоронної стагнації в Україні, обґрунтовано необхідність розвитку екологічно чистих технологій та переходу до нової філософії виробництва, проаналізовано складність та неоднозначність процесу екологічної модернізації виробництва, розкрито історичні аспекти впровадження екологічних інновацій, узагальнено сучасні тенденції екологізації виробництва, доведено необхідність досягнення відповідності вітчизняного виробництва світовим екологічним стандартам, узагальнено принципи побудови та реалізації ефективної національної програми екологізації виробництва для досягнення сталого розвитку.Наукова новизна результатів дослідження. Удосконалено класифікацію факторів, які впливають на ефективність екологічної модернізації економіки; набула подальшого розвитку теорія переходу державної природоохоронної діяльності від директивного регулювання до створення відповідного бізнесового середовища, яке б сприяло впровадженню екологічних інновацій у виробництво.Практична значущість результатів дослідження. Реалізація запропонованого в публікації комплексу заходів дозволить побудувати гнучку та ефективну систему втручання держави в механізми формування екологічної політики на різних рівнях управління; підвищити конкурентоспроможність вітчизняних виробників на світових і регіональних ринках; суттєво збільшити частку фірм, основною діяльністю яких є екологічне підприємництво і екобізнес; істотно покращити умови для залучення екоінвестицій; досягти високого рівня екологічної свідомості громадян.Ключові слова: екологічна модернізація; сталий розвиток; екологізація виробництва; екологічні стандарти; природоохоронна діяльність; екологічна політика; екологічно чисті технології; екологічні ризики; інноваційна діяльність; національна програма екологізації; конкурентні переваги. Печенюк А.В., Печенюк А.П. ЭКОЛОГИЧЕСКАЯ МОДЕРНИЗАЦИЯ ЭКОНОМИКИ КАК НЕОБХОДИМОЕ УСЛОВИЕ УСТОЙЧИВОГО РАЗВИТИЯ ОБЩЕСТВАЦель. Исследование предпосылок экологизации производства в Украине и обоснование механизма реализации эффективной экологической модернизации производства.Методика исследования. Теоретической и методологической базой исследования стали фундаментальные положения современной экономической науки и результаты исследований ученых в области экологизации производства. При этом использован ряд общенаучных методов: теоретического обобщения – для исследования исторических аспектов становления и развития экологической модернизации производства; анализа и синтеза – при определении факторов, сдерживающих темпы внедрения новейших экологобезопасных технологий в Украине; управленческого моделирования – для разработки комплекса мероприятий по активизации экологической модернизации производства; логический – для обоснования преимуществ, которые получает предприятие, инвестируя ресурсы в высокотехнологичные экологобезопасные технологии.Результаты исследования. Исследованы негативные последствия антропогенного воздействия на окружающую среду, раскрыты предпосылки природоохранной стагнации в Украине, обоснована необходимость развития экологически чистых технологий и перехода к новой философии производства, проанализированы сложность и неоднозначность процесса экологической модернизации производства, раскрыты исторические аспекты внедрения экологических инноваций, обобщены современные тенденции экологизации производства, доказана необходимость достижения соответствия отечественного производства мировым экологическим стандартам, обобщены принципы построения и реализации эффективной национальной программы экологизации производства для достижения устойчивого развития.Научная новизна результатов исследования. Усовершенствована классификация факторов, влияющих на эффективность экологической модернизации экономики; получила дальнейшее развитие теория перехода государственной природоохранной деятельности от директивного регулирования к созданию соответствующей бизнес-среды, которая бы способствовала внедрению экологических инноваций в производство.Практическая значимость результатов исследования. Реализация предложенного в публикации комплекса мероприятий позволит построить гибкую и эффективную систему вмешательства государства в механизмы формирования экологической политики на разных уровнях управления; повысить конкурентоспособность отечественных производителей на мировых и региональных рынках; существенно увеличить долю фирм, основной деятельностью которых является экологическое предпринимательство и экобизнес; существенно улучшить условия для привлечения экоинвестиций; достичь высокого уровня экологического сознания граждан.Ключевые слова: экологическая модернизация; устойчивое развитие; экологизация производства; экологические стандарты; природоохранная деятельность; экологическая политика; экологически чистые технологии; экологические риски; инновационная деятельность; национальная программа экологизации; конкурентные преимущества. Pecheniuk A.V., Pecheniuk A.P. ECOLOGICAL MODERNIZATION OF THE ECONOMY AS A NECESSARY CONDITION FOR SUSTAINABLE DEVELOPMENT OF SOCIETYPurpose. The aim of the article is the investigation of the preconditions for ecologization of production and substantiation of the mechanism of implementation of effective environmental modernization of production in Ukraine.Methodology of research. The theoretical and methodological basis of the research became the fundamental positions of modern economic science and the results of research by scientists in the field of environmental production. In this case, a number of general scientific methods are used: theoretical generalization – to study the historical aspects of the formation and development of environmental modernization of production; analysis and synthesis – in determining the factors that restrain the pace of implementation of the latest ecologically safe technologies in Ukraine; managerial modeling – to develop a set of measures for activation the environmental modernization of production; logical – to justify the advantages that the enterprise obtains by investing resources in high-tech ecologically safe technologies.Findings. The negative effects of anthropogenic impact on the environment were investigated, the prerequisites of environmental stagnation in Ukraine were clarified, the necessity of the development of eco-friendly technologies and the transition to a new production philosophy was substantiated, the complexity and ambiguity of the process of environmental modernization of production were analyzed, historical aspects of the implementation of environmental innovations were revealed, the modern tendencies of ecologization of production, the necessity to achieve the conformity of domestic production with the world ecologist standards is proved generalized principles of construction and implementation of effective national greening program production for sustainable development.Originality. The classification of factors that influence the efficiency of ecological modernization of the economy is improved; the theory of the transition of state environmental protection activities from policy regulation to the creation of a suitable business environment, which would contribute to the implementation of environmental innovations in production, has become further developed.Practical value. The implementation of the proposed package of measures proposed in the publication will allow for the construction of a flexible and effective system of state intervention in the mechanisms of the formation of environmental policy at different levels of management; to increase the competitiveness of domestic producers in the world and regional markets; to substantially increase the share of companies, the main activities of which are environmental business and eco-business; to substantially improve the conditions for attracting eco-investments; to achieve a high level of environmental consciousness of citizens.Key words: ecological modernization; sustainable development; ecologization of production; environmental standards; environmental protection; ecological policy; eco-friendly technologies; environmental risks; innovation activity; national ecologization program; competitive advantages.